2001
DOI: 10.1054/bjoc.2001.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the BRCA1 and BRCA2 genes in patients with bilateral breast cancer

Abstract: Summary Mutations of the BRCA1 or BRCA2 genes have been shown to strongly predispose towards the development of contralateral breast cancer in patients from large multi-case families. In order to test the hypothesis that BRCA1 and BRCA2 mutations are more frequent in patients with bilateral breast cancer, we have investigated a hospital-based series of 75 consecutive patients with bilateral breast cancer and a comparison group of 75 patients with unilateral breast cancer, pairwise matched by age and family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 42 publications
2
31
2
3
Order By: Relevance
“…The literature is not unanimous about the predictive value of multiple primary (ipsilateral or contralateral) breast cancers for finding a mutation. Our results are in agreement with the studies of Bergthorsson et al (2001), de la Hoya et al (2002 and Ford et al (1998); however, others failed to demonstrate such a predictive value (Couch et al, 1997;Steinmann et al, 2001). Male breast cancer in combination with a family history of breast/ovarian cancer was indicative of finding a BRCA2 mutation (P ¼ 0.002), which is consistent with a recent population-based British study (Basham et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The literature is not unanimous about the predictive value of multiple primary (ipsilateral or contralateral) breast cancers for finding a mutation. Our results are in agreement with the studies of Bergthorsson et al (2001), de la Hoya et al (2002 and Ford et al (1998); however, others failed to demonstrate such a predictive value (Couch et al, 1997;Steinmann et al, 2001). Male breast cancer in combination with a family history of breast/ovarian cancer was indicative of finding a BRCA2 mutation (P ¼ 0.002), which is consistent with a recent population-based British study (Basham et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…More surprisingly, the bilateral breast cancer sub-group showed a lower frequency of detected BRCA1 mutations (10%). It has been demonstrated that patients with hereditary breast cancer have a higher risk of contralateral breast cancer (Steinmann et al 2001). However, the number of bilateral cases (n=10) screened in our work was probably insufficient compared with those observed in other studies.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, it has been demonstrated that patients with hereditary breast cancer have a higher risk of developing contralateral breast cancer (Steinmann et al 2001). Fortunately, different strategies for reducing this risk are available, including oophorectomy, mastectomy and chemoprevention (Narod et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical history of our patients provided no evidence to suggest that our series might include cases of familial breast cancer, and the high mean age of our patients supports this assumption. Bilaterality does not necessarily reflect a genetic predisposition, 44 unless it is associated with an early age of onset 45 Tumor allelotyping is considered a powerful method for examining the clonal origin of multiple malignancies. [46][47][48] Allelotyping provides a single tumor-specific 'cytogenetic fingerprint' with a high, but limited, number of molecular markers investigated.…”
Section: Discussionmentioning
confidence: 99%